1984
DOI: 10.1111/j.1365-2710.1984.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drug Information Queries Received by the Pharmacy in a Large Psychiatric Hospital

Abstract: SUMMARY Drug information queries were analysed over a representative period of 10 weeks in a 1,300 bed psychiatric hospital. A total of 90 queries were answered; 30 of these related to psychiatric drugs but 60 were concerned with general medical conditions. Half the number of questions came from doctors who, in presenting a diagnosis, were asking for information on the most appropriate therapy available. Queries from nurses formed the bulk of the remainder. The results of the survey disprove the misconception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Although the number of queries from dentists was small (<1 %), other studies have not reported queries from this group. The total number of queries received per month in our centre of 134 was much higher than those reported (28, 27 and 9, respectively) from earlier studies [11][12][13] . The high utilization of this service may be due to three factors-the size of the institution, location (developing country) and the timing of the study (recent).…”
contrasting
confidence: 70%
“…Although the number of queries from dentists was small (<1 %), other studies have not reported queries from this group. The total number of queries received per month in our centre of 134 was much higher than those reported (28, 27 and 9, respectively) from earlier studies [11][12][13] . The high utilization of this service may be due to three factors-the size of the institution, location (developing country) and the timing of the study (recent).…”
contrasting
confidence: 70%
“…A significant proportion of clinical pharmacy interventions in this study related to non-psychotropic drug therapy. In an analysis of drug information enquiries to pharmacy staff at a large psychiatric hospital, O'Hare et al found that two-thirds of all queries related to the use of non-psychotropic drugs (17). Furthermore, Williams and Betley identified the substantial potential for inappropriate nonpsychotropic drug therapy in nursing home facilities, suggesting that the opportunity for clinical pharmacy intervention directed at improving patient outcomes also exists in this setting (18).…”
Section: Discussionmentioning
confidence: 99%
“…The Lancet and Brirish Medical Journal outranked all other journals in the level of citation frequency and apart from established journals the local pharmacy bulletin featured prominently as a frequent reference source for drug related inquiries. (9). T h u s the formalised D I C and the ward/clinical pharmacy service have developed in a complementary fashion, the D I C tending to deal with a considerable number of drug-related inquiries that normally would have with the ward/clinical pharmacist being increasingly recognised as a therapeutic consultant (10).…”
Section: Utilisarion Of Primary Rejerence Sourcesmentioning
confidence: 99%